The addition of idarucizumab to plasma samples containing dabigatran allows the use of routine coagulation assays for the diagnosis of hemostasis disorders. (5th October 2015) - Jacquemin, M.; Toelen, J.; Schoeters, J.; van Horenbeeck, I.; Vanlinthout, I.; Debasse, M.; Peetermans, M.; Vanassche, T.; Peerlinck, K.; van Ryn, J.; Verhamme, P.
Summary: Background: The anticoagulant effect of dabigatran can be approximated by its prolongation of routine coagulation assays. Consequently, dabigatran also interferes with thrombophilia screening or with diagnosing hemostasis disorders that have developed after the initiation of anticoagulant treatment, such as vitamin K deficiency or acquired hemophilia A. Objectives: This study was carried out to determine whether idarucizumab, a humanized antibody fragment that binds dabigatran, could fully neutralize dabigatran in routine diagnostic coagulation assays conducted in vitro, thereby preventing false‐positive or false‐negative diagnostic readouts. Methods: Preliminary experiments identified coagulation assays that were sensitive to dabigatran, and identified a concentration of idarucizumab that neutralized the effects of dabigatran. These assays were then carried out with patient and control plasma samples spiked with dabigatran, with or without a molar excess of idarucizumab. Results: Dabigatran altered the prothrombin time, activated partial thromboplastin time and thrombin time, and the measurement of intrinsic and extrinsic factor levels. Screening and confirmation tests used for lupus anticoagulant detection were prolonged by dabigatran, falsely suggesting the presence of lupus anticoagulant. Conversely, the addition of dabigatran falsely corrected an abnormal activated protein C resistance ratio. Addition of idarucizumab completely normalized these measurements, and allowed the correct identification of normal and abnormal samples with these assays. Conclusions: In vitro addition of idarucizumab to plasma samples containing dabigatran fully neutralizes the drug, and facilitates the use of routine coagulation assays to allow the diagnosis of hemostasis disorders that may be concurrently present in patients taking dabigatran.